A longitudinal study of the acquisition of verbal morphology in the EFL classroom - Semren, Mirjana (ELOPE (Ljubljana), 2017)
This paper investigates the order of the acquisition of grammatical morphemes in the interlanguage of Croatian pupils of English as a foreign language (EFL). The order of acquisition was determined for nine grammatical morphemes. Additionally, the selected morphemes were combined to form the four verb tenses so as to determine the order of their emergence in the pupils' verb-morphology repertoire. The study was conducted on a corpus of 36 transcribed recordings of parts of classroom interaction. The pupils' speech production was elicited by various task-based activities. The suppliance of nine grammatical morphemes was investigated by means of obligatory occasion analysis (Brown 1973) which examined their obligatory and correct use. The obtained results revealed progress only in the acquisition of the present tense copula be. The emergence of verb tenses was partly identified due to the insufficient suppliance of grammatical morphemes in the pupils' speech production.
Keywords: angleščina; English; glagolski časi; na nalogah temelječe dejavnosti; obvezno sobesedilo; slovnični morfemi; vrstni red usvajanja